2022
DOI: 10.1016/j.pedneo.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Feeding difficulties in Asian children with autism spectrum disorder

Abstract: Background: To characterize the nature and severity of feeding difficulties in Asian young children with Autism Spectrum Disorders (ASD) and identify potential predictors of poorer feeding outcomes.Methods: Cross sectional study of children aged 1e7 years with ASD. Parents completed the following: demographic information, brief autism mealtime behavior inventory, aberrant behavior checklist (ABC), behavioral pediatrics feeding assessment scale (BPFAS) and caregiver feeding style questionnaire. Additional infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
2
7
1
Order By: Relevance
“…When exploring the nature of feeding difficulties in our cohort of autistic children, we found that the proportion of children who experienced significant feeding difficulties (69%) was similar to those reported in previous studies (Adams et al, 2021; Kang et al, 2021). However, despite this high frequency of feeding difficulties in autistic children, it should be noted that methodological rigor varied across these studies (Sharp et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…When exploring the nature of feeding difficulties in our cohort of autistic children, we found that the proportion of children who experienced significant feeding difficulties (69%) was similar to those reported in previous studies (Adams et al, 2021; Kang et al, 2021). However, despite this high frequency of feeding difficulties in autistic children, it should be noted that methodological rigor varied across these studies (Sharp et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The feeding problem is the most common topic among parents regarding mealtimes. Beyond the behavioral, social, and communication difficulties, co-morbid feeding problems are a considerable challenge for parents and providers since autism spectrum disorder is linked with a wide range of feeding issues [ 50 ]. Undeniably, the prevalence rate of underweight or overweight and obese children with autism spectrum disorder is higher than the typically developing children of the same age; and it was said to be due to autistic children’s food selectivity behavior [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parenting and feeding styles have a significant impact on a child’s weight and food consumption. Nonetheless, the studies are still not strong among the autism spectrum disorder population [ 50 ]. In general, parent strategies that help increase food acceptability in children consist of preparing a wide range of meals available in the household, consistently introducing the child to new and similar foods, providing positive encouragement, and parental modeling [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding obstacles are commonly encountered in children with autism and their families. Certain troubles are linked to food discernment and food refusal and are more likely focused than those related to mealtime (Bonsall et al, 2021;Kang et al, 2022). Recent studies from Saudi Arabia have shown relatively low awareness levels of autism (Sabbagh et al, 2021;Abualhommos et al, 2022;Alyami et al, 2022).…”
Section: Medical Sciencementioning
confidence: 99%